Enhancing Students’ Speaking Mastery by Using Chain Drill Technique - Rayendriani Fahmei Lubis; Melati Suri (English Education : English Journal for Teaching and Learning, 2022)
The purposes of this research were to know the effect of Chain Drill Technique on students’ speaking skill mastery. The sample of this research consisted of 12 students at grade X-A as experimental class and 10 students at grade X-B as control class MA Syekh Ahmad Basyir Batangtoru. This research is categorized into experimental research through pre-test and post-test design. Data collected by using oral test form and analyzed by using t-test formula. The result of research showed mean score in pre-test of experimental class was 43,5 and control class was 47.1. Meanwhile, the mean score of experimental class in post-test was 71.5 and control class was 53,5. In addition, after doing T-test, the researcher found that the posttest in experimental class was tcountttable (3.161.76). It can be concluded that there was significant effect of Chain Drill Technique on Students’ Speaking mastery.